The transmission of resilience learning in the context of formal education an ethnomusicological review - Irawati, Eli (Linguistics and Culture Review, 2021)
The existence and continuity of musical practice in the world, among others, is strongly influenced by transmission or inheritance. Therefore, local-traditional music in Indonesia that lives and develops in the midst of oral culture becomes important to study transmission. This study aims to determine the transmission process of learning in the Kalimantan Music class and find the right formula for delivering teaching materials. This research is qualitative research with an applied ethnomusicology approach. The method of collection is through observation, interviews and supported by documentation and literature searches. The research was conducted at the Department of Ethnomusicology, Faculty of Performing Arts, Indonesian Institute of the Arts, Yogyakarta. The study results indicate that it is important to incorporate learning models and strategies from the teacher to the Kalimantan Music class. They are practicing analytical-based learning methods in the context of a resilient society. Chunking-based strategies and formulas in memorizing songs or reports that are played are made into two notation systems, namely block notation and pronunciation-based notation, to make it easier for students to play music. Block notation formulas and pronunciation-based notations can be applied as a way of learning music in class.